PROFIL LKS PENGAMATAN BERORIENTASI METODE STUDENT FACILITATOR AND EXPLAINING PADA MATERI SPERMATOPHYTA KELAS X SMA - SUBEKTI, BAMBANG (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
The research of development of observational student worksheet oriented on Student Facilitator And Explaining (SFAE) method in seed plant (Spermatophyta) matter was aimed to produce feasible worksheets based on the theoretical and empirical aspects and to describe the feasibility based on the theoretical aspects by validation and empirical aspects by student activity observations and student’s response after using the worksheets. This research was conducted using the 4-D models consists of four stages, those are: define, design, develop, and dessiminate. The dessiminate not been done. Theoretical feasibility of the validation theoretically got a percentage of 66.67% to 100.00% with fairly to very good interpretation. Empirical feasibility based on observations of student activity got a percentage of 65.00% to 100.00% with fairly to very good interpretation, while the response from the students get a percentage of 95.42 % with a very good interpretation. Key words: Observational student worksheet, Student Facilitator And Explaining methode, Spermatophyta.